Eugenia coetzalensis (Myrtaceae), a new species from central Veracruz, Mexico - Durán-Espinosa, Carlos; Castillo-Campos, Gonzalo; López-Ortega, Maurilio (Phytotaxa, 2018)
This article describes and illustrates the new species Eugenia coetzalensis, considered as endemic to central Veracruz and northern Oaxaca. E. coetzalensis is part of the tree stratum of the subdeciduous tropical forest, growing on Ortic Luvisol with Lithosol soils, at altitudes ranging from 282 to 507 m elev. This taxon shows similarities with Eugenia praeterita, Eugenia naraveana and Eugenia chahalana; however, there are clear morphological differences that separate them; such as bark color, in leaflet and acumen size, number of secondary veins, racemose inflorescences, and flowers per axilla, as well as the shape and size of its fruits.